2020
DOI: 10.1096/fj.201903281r
|View full text |Cite
|
Sign up to set email alerts
|

Rhophilin‐associated tail protein 1 promotes migration and metastasis in triple negative breast cancer via activation of RhoA

Abstract: Triple negative breast cancer (TNBC) is the most aggressive breast cancer subtype with high motile and invasive capacity that contributes to metastasis. Understanding the mechanisms for the motility of TNBC might provide novel targetable vulnerabilities of the tumors. Herein, we find that Rhophilin-associated tail protein 1 (ROPN1) is selectively overexpressed in human TNBC cell lines and tissues. Overexpression of ROPN1 promotes, while silencing of ROPN1 inhibits the robust migration, invasion, and in vivo me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The striking abundance and homogeneity of ROPN1/B in TNBC likely limit the risk of tumor recurrence following ACT since it is reported that outgrowth of antigen-negative tumor cell clones is generally a consequence of low and heterogeneous expression of target antigens within tumors [48][49][50] . Notably, a recent report highlighted that ROPN1 may act as an oncogene and drive metastasis formation in vivo and demonstrated an inverse correlation between ROPN1 expression and survival of TNBC patients 51 , further highlighting the therapeutic value of ROPN1 as a target for ACT.…”
Section: Discussionmentioning
confidence: 99%
“…The striking abundance and homogeneity of ROPN1/B in TNBC likely limit the risk of tumor recurrence following ACT since it is reported that outgrowth of antigen-negative tumor cell clones is generally a consequence of low and heterogeneous expression of target antigens within tumors [48][49][50] . Notably, a recent report highlighted that ROPN1 may act as an oncogene and drive metastasis formation in vivo and demonstrated an inverse correlation between ROPN1 expression and survival of TNBC patients 51 , further highlighting the therapeutic value of ROPN1 as a target for ACT.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, Rhophilin-1 and its orthologues contain the N-terminal domain, ROPN1, which interacts with A-kinase anchor protein 3 (AKAP3) in both GDP- and GTP-bound RhoA in vitro. ROPN1 binding regulates the actin cytoskeleton by interacting with various downstream molecules [ 31 , 32 ]. Its N-terminal domain is interesting since it is found in only a few proteins [ 28 , 33 ].…”
Section: Introductionmentioning
confidence: 99%